2022
DOI: 10.1007/s11192-022-04308-7
|View full text |Cite
|
Sign up to set email alerts
|

Are female scientists less inclined to publish alone? The gender solo research gap

Abstract: In solo research, scientists compete individually for prestige, sending clear signals about their research ability, avoiding problems in credit allocation, and reducing conflicts about authorship. We examine to what extent male and female scientists differ in their use of solo publishing across various dimensions. This research is the first to comprehensively study the “gender solo research gap” among all internationally visible scientists within a whole national higher education system. We examine the gap thr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 132 publications
(176 reference statements)
1
16
0
1
Order By: Relevance
“…Existing studies on sole authorship seem to agree that women write a smaller proportion of their publications alone (West et al, 2013 ; Ductor et al, 2018 ; Sarsons et al, 2021 ; Yamamoto and Frachtenberg, 2022 ). In one of the few works addressing the question of gender and solo research in more detail, however, Kwiek and Roszka ( 2022 ) find only marginal gender differences among researchers at Polish universities. They formally introduce the gender solo research gap and extensively study its underlying hypothesis that “female scientists are less involved in publishing alone than male scientists.” They find statistically significant gender differences only among young academics, and with rather small effect.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Existing studies on sole authorship seem to agree that women write a smaller proportion of their publications alone (West et al, 2013 ; Ductor et al, 2018 ; Sarsons et al, 2021 ; Yamamoto and Frachtenberg, 2022 ). In one of the few works addressing the question of gender and solo research in more detail, however, Kwiek and Roszka ( 2022 ) find only marginal gender differences among researchers at Polish universities. They formally introduce the gender solo research gap and extensively study its underlying hypothesis that “female scientists are less involved in publishing alone than male scientists.” They find statistically significant gender differences only among young academics, and with rather small effect.…”
Section: Related Workmentioning
confidence: 99%
“…For example, research has shown for various disciplines that the network size, i.e., the number of one's distinct coauthors, is positively correlated with a larger number of citations (Wuchty et al, 2007 ; Sarigöl et al, 2014 ; Servia-Rodríguez et al, 2015 ) and higher productivity (Ductor, 2015 ; Servia-Rodríguez et al, 2015 ). At the same time, publishing in groups reduces various risks, such as openly hostile criticism or the responsibility for errors (Kwiek and Roszka, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that full professors were the most productive: the "higher the more productive" principle applied to all academic ranks, and male scholars were more productive than female scholars for all publication types (Puuska 2020: 428-430). Full professors were also more productive than lower ranks in the soft sciences, where solo research is important, and therefore the impact of leading large research grants is marginal (see Kwiek & Roszka 2022a). In several male-dominated fields, female full professors were shown to be more productive than male full professors, which may indicate that in these fields only exceptionally productive women are appointed to full professorships, whereas in other fields, possibly less merit in research is required for women in this rank (Puuska 2010: 435).…”
Section: All Ranks Literature: International Insightsmentioning
confidence: 99%
“…Either nationally or globally, the contributions of women scientists have been measured in different dimensions including gender gap in scientific output (see for example Kretschmer and Kretschmer 2013;Lewison and Markusova 2011), the comparative contribution of women of different countries as well as different subject fields (see for example Muñoz-Muñoz 2005;Nourmohammadi and Hodaei 2014). Several studies on gender have shown a https://www.newindianexpress.com/nation/2019/jul/13/ 2896-scientist-posts-lying-vacant-in-70-institutesunder-ministry-of-science-and-technology-govern-2003071.html that women scientists tend to publish fewer articles than their male colleagues of the same age (Abramo and D'Angelo 2009;Duch et al 2012;Kwiek and Roszka 2022;Bird 2011;Zuckerman 1991), publish papers in less reputed journals (Holman, Stuart-Fox and Hauser 2018;Lerback and Hanson 2017;Lerchenmüller, Lerchenmueller and Sorenson 2018) and received fewer citations (Caplar, Tacchella and Birrer 2016;King et al 2017;Larivière et al 2013). An explanation of low contribution by women has been pointed out by Ward and Grant (1996), where they mentioned that the female scientists devote more time to teaching and administrative work, while the male scientists focus more on the research and supervision of doctoral students.…”
Section: Literature Reviewmentioning
confidence: 99%